Leydig cell hyperplasia of ovary - An unusual finding in postneoadjuvant chemotherapy case of primary fallopian tube carcinoma - Kriti Chaturvedi; Meenakshi Rao; Souvik Saha; Jeewan Ram Vishnoi; Aasma Nalwa (Wolters Kluwer Medknow Publications, 2022)
A large number of high-grade serous ovarian carcinomas originate in the fallopian tubes. Neoadjuvant chemotherapy followed by surgery may lead to a number of chemotherapy-induced changes in the ovary, which may lead to an erroneous diagnosis. We present a rare case of a 55-year-old postmenopausal woman who was clinically diagnosed with carcinoma of the right ovary; on histopathologic evaluation after neoadjuvant chemotherapy, the primary site was found to be the right fallopian tube. The right ovary showed chemotherapy-related changes along with extensive Leydig cell hyperplasia. As the presence of Leydig cell hyperplasia in this setting is an unusual finding, it may pose a diagnostic dilemma for the pathologist; so an awareness of this entity is important to avoid misdiagnosis.